2012
DOI: 10.1111/j.1600-0838.2011.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative factors predicting good outcome in terms of health‐related quality of life after ACL reconstruction

Abstract: The life situation of many patients changes after an anterior cruciate ligament (ACL) rupture and subsequent reconstruction, and this may affect their health-related quality of life in many ways. It is well known that the overall clinical results after ACL reconstruction are considered good, but pre-operative predictive factors for a good post-operative clinical outcome after ACL reconstruction have not been studied in as much detail. The purpose of this study was to identify pre-operative factors that predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Lepley and Palmieri-Smith45 (level B) showed that preoperative quadriceps strength is positively related to postoperative quadriceps strength at the moment of return to play. Månsson et al 46 (level C) found that a higher preoperative Tegner activity level predicts a better outcome at a minimal follow-up of 22 months. Quelard et al 49 (level B) described that a limited preoperative ROM and female sex account for a limited ROM 3 months postoperative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lepley and Palmieri-Smith45 (level B) showed that preoperative quadriceps strength is positively related to postoperative quadriceps strength at the moment of return to play. Månsson et al 46 (level C) found that a higher preoperative Tegner activity level predicts a better outcome at a minimal follow-up of 22 months. Quelard et al 49 (level B) described that a limited preoperative ROM and female sex account for a limited ROM 3 months postoperative.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that a preoperative full extension ROM reduces the chance for postoperative complications as arthrofibrosis 46 48. Moreover, a deficit in quadriceps strength of 20% or more predicts a significant strength deficit until 2 years after ACLR (level 2) 41 121.…”
Section: Consensus Conclusionmentioning
confidence: 99%
“…Previous studies [25][26][27][28][29][30][31] documented the effect of meniscectomy on the development of OA after ACL reconstruction. As reported in the results, despite the relatively low number of meniscectomies performed in group I, a higher grade of OA between meniscectomized and unmeniscectomized patients was found in all radiologic scale used; however, in group II there was no difference between meniscectomized and unmeniscectomized patients according to Fairbank and Kellgren classification.…”
Section: Discussionmentioning
confidence: 98%
“…Eitzen et al found lower bodily pain subscores at two years in subjects with concomitant ACL reconstruction and meniscal injuries requiring treatment, but subjects who had meniscal injuries requiring repair were excluded from that study 20 . Månsson et al examined baseline predictors of health-related quality of life using the SF-36 at three to six years following ACL reconstruction and found that the pre-injury activity level was a predictor of two of the SF-36 subscales 21 . Specifically, a higher baseline Tegner activity level was associated with higher general health scores and lower role emotional scores, whereas we did not find activity level to predict outcome.…”
Section: Discussionmentioning
confidence: 99%